Strategies for Stabilizing Atomically Dispersed Metal Catalysts. Issue 1 (18th December 2017) - Qin, Ruixuan; Liu, Pengxin; Fu, Gang; Zheng, Nanfeng
Abstract: Atomically dispersing metal atoms on supports provides an ideal strategy for maximizing metal utilization for catalysis, which is particularly important for fabricating cost‐effective catalysts based on Earth‐scarce metals. However, due to the high surface energy and thus instability of single atoms, it remains challenging to fabricate stable atomically dispersed metal catalysts. Here, strategies for stabilizing atomically dispersed metal catalysts on various supports are summarized. Based on strategies to enhance the interaction between the metal and the support to prevent the sintering of metal atoms, several approaches to stabilize supported atomically dispersed metal catalysts are then extensively discussed. To close, the importance of the interface species surrounding single atoms in determining the catalytic properties of atomically dispersed metal catalysts is discussed, together with a summary of the prospects for the development of the field. Abstract : Atomically dispersed metal catalysts are emerging as a new generation of heterogeneous catalysts. The general strategies to stabilize single metal atoms on various supports are summarized. Together with surface‐dispersed mononuclear organometallics and micropore‐confined single metal atoms, strategies to stabilize single metal atoms on the surfaces of both metal‐containing and metal‐free supports are discussed.